Β-Blockers and angiotensin-converting enzyme inhibitors with sublingual immunotherapy: are risks related to individual product safety profile?. Issue 4 (August 2020) - Smith, Derek M.; Coop, Christopher A.; Freeman, Theodore M.
Abstract : Purpose of review: The objective of this article is to review the available literature regarding the risks associated with sublingual immunotherapy and angiotensin-converting enzyme (ACE) inhibitors or β-blocker use. It also evaluates for any differences in these risks among the available sublingual immunotherapy (SLIT) tablets. Recent findings: A literature search was conducted in PubMed to identify peer-reviewed articles using the following keywords: anaphylaxis, ACE inhibitor, β-blocker, and sublingual immunotherapy. Minimal data exist regarding their safety of SLIT in patients concomitantly taking ACE inhibitors or β-blockers. The adverse reaction rates seem similar between SLIT products. Summary: A risk-versus-benefit discussion should be communicated with the patient taking a β-blocker before beginning SLIT but automatic denial of SLIT to these patients is not warranted.